2018
DOI: 10.1016/j.jaci.2017.12.772
|View full text |Cite
|
Sign up to set email alerts
|

Identification of a relevant allergen in the induction of rhinoconjuntivitis in subjects sensitized to peach pollen

Abstract: RATIONALE: Patients can be allergic to multiple substances due to IgEmediated recognition of similar epitopes on proteins from different sources. We applied cluster-detection techniques to food-allergic patient data to detect groups of cross-reactive allergens. Such groupings will be useful for patient-classification, diagnosis, treatment and discovery. METHODS: Skin prick test (SPT) results were obtained for confirmed food-allergic patients, for allergens common to Mediterranean areas. Patients/allergens with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…The data shown in this study provide important and new information about allergens of PT pollen, with specific focus on a novel allergen, named as Pru p 9 [20,21] by the WHO-IUS PLOS ONE nomenclature committee. It belongs to PR-1a protein family, relevant for the induction of respiratory and ocular symptoms in allergic patients, independently whether they were directly or indirectly exposed [28]. Although it has been shown that PT allergens presented in leaves and branches can induce both upper and lower airway symptoms in exposed workers, the association between symptoms and specific allergens from the pollen was not verified [14,15].…”
Section: Discussionmentioning
confidence: 99%
“…The data shown in this study provide important and new information about allergens of PT pollen, with specific focus on a novel allergen, named as Pru p 9 [20,21] by the WHO-IUS PLOS ONE nomenclature committee. It belongs to PR-1a protein family, relevant for the induction of respiratory and ocular symptoms in allergic patients, independently whether they were directly or indirectly exposed [28]. Although it has been shown that PT allergens presented in leaves and branches can induce both upper and lower airway symptoms in exposed workers, the association between symptoms and specific allergens from the pollen was not verified [14,15].…”
Section: Discussionmentioning
confidence: 99%